Local estradiol deposition in a rat rotator cuff repair model: proof of concept - Peter N. Chalmers, MD; Michael J. Jurynec, PhD; Austin M. Hickey, MS; T. Wade Fallin, MS; Antonio C. Zelada, BS; Matthew Honeggar, BS; James M. Hotaling, MD; Benjamin Emery, MPhil; Robert Tashjian, MD (JSES International)
Background: Local delivery of hormones could potentially provide local benefits to bone and enthesis while avoiding systemic side effects. The objective of this study was to demonstrate proof of concept for local deposition of estradiol in a rat rotator cuff repair model. Methods: First, in vitro elution studies using an injection-molded polycaprolactone (PCL) implant were performed. Second, PCL rods laden with 5% estradiol were implanted within the greater tuberosity of 14 ovariectomized wild-type Sprague-Dawley rats with a concomitant rotator cuff repair. Rods without hormone were implanted in 4 ovariectomized rats and 4 intact rats as controls. We analyzed (1) postimplantation serum estradiol levels via enzyme-linked immunoassay, (2) tissue hormone levels via liquid chromatography-mass spectrometry, and (3) bone mineral density (BMD) of the postimplantation humerus via micro-computed tomography. Results: In vitro elution studies demonstrated 2 weeks of controlled estradiol release at an average daily dose of 10.9 μg/day, with continued release of at least 35 days. Serum estradiol levels significantly increased from 5 ± 1 preoperatively, to 972 ± 251, to 831 ± 477 pg/mL at 6 days postoperatively (P < .001). Tissue estradiol levels were significantly higher within the rotator cuff tendon adjacent to the implant (45.9 ± 80.3 pg/mg) than in control tendon tissues (1.4 ± 1.3 pg/mg; P = .002). Micro-computed tomography demonstrated significantly higher BMD adjacent to estradiol-laden implants than control implants at 6 days postoperatively (1462 ± 57 vs. 1291 ± 69 hydroxyapatite/cc; P < .001). Conclusion: This study demonstrates that a PCL implant is capable of sustained release of estradiol over 6 weeks and concentrates estradiol locally. Local deposition of estradiol increases local BMD rapidly.